Journalism education and fake news : a literature review - Vukić, Tijana (Array, 2021)
This article offers a scholarly review of the literature and research on journalism education and fake news from an international and a local (Croatian) perspective. The purpose of this paper is to examine the connection between the education for journalists as a scholarly and academic discipline (as well as a teaching practice) and the issues caused by fake news in the digital age of mass media. Based on a comprehensive critical conceptual analysis of the body of knowledge available on the subject, it was determined that there is a diverse discussion about the status of journalism education regarding fake news. In that context, fake news has so far been internationally researched from several angles – curriculum content, journalism students, journalism and media studies, journalism practice, media audience, etc. When addressing the issue of education of journalists and fake news, three streams can be singled out. The first and most voluminous one refers to the systematic formal or additional education regarding media and information literacy. The next one refers to various changes related to the higher education system for the education of journalists, but without any concrete propositions for system reconstruction or upgrading. The last one advocates providing additional professional education to employed journalists. From the local perspective, even though only two articles suggest journalism education as a solution for the problems caused by fake news, based on thorough research it can be concluded that fake news and journalism education are not yet topics of interest among communication scholars in Croatia.